ANALISIS DAMPAK VARIABEL MAKROEKONOMI TERHADAP NERACA PEMBAYARAN DENGAN INDEKS PERSEPSI KORUPSI SEBAGAI VARIABEL MODERASI DI ASEAN-6 BERDASARKAN PERSPEKTIF EKONOMI ISLAM - Hasbiah; Karfin; Fatima Az-zahra Wairooy (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This study employs an Islamic economic perspective to investigate the impact of macroeconomic factors on the Balance of Payments (BOP) in ASEAN-6 countries, incorporating the Corruption Perception Index (CPI) as a moderating variable. Utilizing panel data regression and moderated regression analysis (MRA), panel data regression is carried out in two stages, namely in the first stage determining the estimation model, it must be known first which model is the best between CEM, FEM and REM. The second stage is the selection of the estimation model starting from the Chow test, Hausman test and Lagrange Multiplier (LM) test. the study examines data from Transparency International (TI) and the World Bank. A total of 168 samples from Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam were analyzed. The results indicate that while tourism, inflation, and exchange rates do not significantly affect the BOP, both portfolio investment and net exports have a substantial positive impact. Additionally, the CPI is found to be a significant moderating variable. The study’s findings suggest several strategies for managing volatile global economic conditions, highlighting the importance of focusing on variables that positively influence the BOP. These insights can guide the ASEAN-6 governments in maintaining or enhancing factors that contribute to a stable BOP, ensuring economic resilience in the region